Femtosecond Laser Written Plane-by-Plane Bragg Grating Sensors in Bioresorbable Phosphate Optical Fibres - Theodosiou, Antreas; Janner, Davide; Kalli, Kyriacos; Boetti, Nadia G.; Ceci-Ginistrelli, Edoardo; Pugliese, Diego; Milanese, Daniel (My University, 2019)
We report on the realization of different types of optical sensors in a bioresorbable phosphate glass optical fiber using a femtosecond laser operating at 517 nm. We inscribed fiber Bragg grating-based optical filters such as uniform Bragg gratings, chirped gratings, and Fabry-Perot cavities, using the plane-by-plane direct write inscription. The gratings were characterized in reflection and tested as sensors for temperature and relative humidity. We studied the stability and resilience of the gratings when inserted in high humidity environments (>95%) for 52 h and observed the evolution of the grating characteristics during this period.
Keywords: Bioresorbable optical fibre; Biosensors; Femtosecond laser; Fibre Bragg gratings